PENGARUH POLA ASUH ORANG TUA, GAYA BELAJAR, DAN MOTIVASI BERPRESTASI TERHADAP PRESTASI BELAJAR MATEMATIKA SISWA MTsN SE-MAKASSAR - Besse Intan Permatasari (MaPan : Jurnal Matematika dan Pembelajaran, 2015)
This research aimed to examine the direct influence and the interaction influence among the parenting style, learning style, and achievement motivation on students’ mathematics learning achievement. This research is ex-post facto research. The population of this research was the students of Madrasah Tsanawiyah Negeri (MTsN) Makassar consisted of 2 schools. Sample was selected by employing purposive random sampling and obtained 4 classes. Technique of analysis which is used is mixed variables regression technique of analysis. The results of the research reveal that (1) the students’ mathematics learning achievement with authoritarian parenting style has no significant difference on the students’ mathematics learning achievement with authoritative parenting style; however, it is better than the student’ mathematics learning achievement with permissive/indulgent or rejecting/neglecting parenting styles. (2) the students’ mathematics learning achievement with visual learning style has no difference on the students’ mathematic learning achievement with auditory learning style; however it is better the students’ mathematics achievement with kinesthetic learning style. (3) the achievement motivation has positive influence on student mathematics learning achievement, (4) there is no interaction influence of parenting style and students’ learning style on mathematics learning achievement, (5) there is no interaction influence of parenting style and students’ motivation achievement on mathematics learning achievement, (6) there is no interaction influence on students’ learning style and achievement motivation on mathematics learning achievement, (7) there is no interaction influence of parenting style, learning style, and achievement motivation on mathematics learning achievement.